2018
DOI: 10.1155/2018/4735752
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PAR4 Upregulates p16 through Inhibition of DNMT1 and HDAC2 Expression via MAPK Signals in Esophageal Squamous Cell Carcinoma Cells

Abstract: A previous study showed that a downexpression of protease-activated receptor 4 (PAR4) is associated with the development of esophageal squamous cell carcinoma (ESCC). In this study, we explored the relationship between PAR4 activation and the expression of p16, and elucidated the underlying mechanisms in PAR4 inducing the tumor suppressor role in ESCC. ESCC cell lines (EC109 and TE-1) were treated with PAR4-activating peptide (PAR4-AP). Immunohistochemistry for DNA methyltransferase 1 (DNMT1) and histone deace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Genes in the turquoise module were enriched in pro-tumorigenic pathways such as MAPK signaling, JAK/STAT signaling, and metabolic pathways ( Figure 4B and D). [12][13][14] In contrast, genes in the yellow module were enriched in key pro-apoptotic pathways including the P53, arachidonic acid metabolism, and pyrimidine metabolism pathways, all of which can suppress oncogenesis. 15,16 Preparation of a lncRNA-mRNA Network…”
Section: Function Enrichment Analyses Of Key Escc-related Modulesmentioning
confidence: 97%
“…Genes in the turquoise module were enriched in pro-tumorigenic pathways such as MAPK signaling, JAK/STAT signaling, and metabolic pathways ( Figure 4B and D). [12][13][14] In contrast, genes in the yellow module were enriched in key pro-apoptotic pathways including the P53, arachidonic acid metabolism, and pyrimidine metabolism pathways, all of which can suppress oncogenesis. 15,16 Preparation of a lncRNA-mRNA Network…”
Section: Function Enrichment Analyses Of Key Escc-related Modulesmentioning
confidence: 97%
“…HDAC inhibitors can treat SCC [ 24 ], and HDAC2 immunoreactivity is enhanced in ESCC tissues [ 8 ]. For clarification of HDAC2-pivoted mechanism in ESCC, we tested HDAC2 expression in 121 cases of ESCC tumor and mucosal tissues, as well as in ESCC cell lines and HEEC by RT-qPCR and Western blot assay.…”
Section: Resultsmentioning
confidence: 99%
“…Of the component of HDACs, HDAC2 takes part in the mediation of ESCC cell proliferation, cell cycle arrest and apoptosis [ 7 ]. Actually, it has been demonstrated that inhibited HDAC2 could enhance apoptosis and repress proliferation of ESCC cells [ 8 ]. MicroRNAs (miRNAs) are vital in the biological behaviors of EC cells, and they are often connected with multi-drug resistance of esophageal cancer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the potential association of PAR4 with cancer progression is controversial. Upregulation of PAR4 is reported to induce apoptosis in prostate and esophageal cancer cells [36][37][38] and suppression of expression shown to trigger aggressive gastric cancer [39] and poor prognosis and recurrence of breast cancer [40,41]. However, PAR4 activation mainly induces progression of colon cancer.…”
Section: Discussionmentioning
confidence: 99%